Software aiding in selection of promising germplasm for oil palm improvement trials: Software aiding in selection of promising germplasm for oil palm improvement trials - K L MARY RANI,; H P BHAGYA,; A SIVANI,; S GOVANDHAN RAO,; P ANITHA,; G RAVICHANDRAN, (Journal of Oilseeds Research, 2020)
Oil palm germplasm of exotic sources collected from different parts of country is conserved in gene bank ofICAR-Indian Institute of Oil Palm Research (ICAR-IIOPR). Data recorded on morphological and yield parametersover a period of time needs to be evaluated to identify promising ones with required characteristics. Software was developed providing data entry screens for recorded observations, data analysis and generating reports which help in selection of germplasm with required traits.